2021
DOI: 10.1101/2021.11.24.21266768
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights from an autism imaging biomarker challenge: promises and threats to biomarker discovery

Abstract: MRI has been extensively used to identify anatomical and functional differences in Autism Spectrum Disorder (ASD). Yet, many of these findings have proven difficult to replicate because studies rely on small cohorts and are built on many complex, undisclosed, analytic choices. We conducted an international challenge to predict ASD diagnosis from MRI data, where we provided preprocessed anatomical and functional MRI data from > 2,000 individuals. Evaluation of the predictions was rigorously blinded. 146 chal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 60 publications
2
8
0
Order By: Relevance
“…Our findings show that these algorithms are capable of inferring Autism diagnosis on the basis of structural MRIs with at least the same level of accuracy as traditional Machine Learning algorithms, while requiring a smaller number of training epochs. The average accuracy score (64.1%) and ROC AUC score (0.67) obtained for participants without comorbidities is consistent with previous Machine Learning models trained on sMRI data (e.g., [39]). The comparable accuracy we achieved should be viewed in the context of the speed of inference of Deep Learning models over Machine Learning approaches.…”
Section: D Deep Learning Applied To Minimally Processed Datasupporting
confidence: 87%
See 3 more Smart Citations
“…Our findings show that these algorithms are capable of inferring Autism diagnosis on the basis of structural MRIs with at least the same level of accuracy as traditional Machine Learning algorithms, while requiring a smaller number of training epochs. The average accuracy score (64.1%) and ROC AUC score (0.67) obtained for participants without comorbidities is consistent with previous Machine Learning models trained on sMRI data (e.g., [39]). The comparable accuracy we achieved should be viewed in the context of the speed of inference of Deep Learning models over Machine Learning approaches.…”
Section: D Deep Learning Applied To Minimally Processed Datasupporting
confidence: 87%
“…There is considerable scope to extend our interpretable Deep Learning pipeline to the prediction of other neurological or neuropsychiatric conditions or to other MRI modalities. Traut et al[39] reported that prediction of Autism was considerably improved (from AUC=0.66 using only anatomical MRI to AUC=0.79 using both anatomical and functional data) for a blended model that incorporated both functional and structural MRI data. Future work will examine whether functional MRI data can also improve our models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…; https://doi.org/10.1101/2023.03. 26.534053 doi: bioRxiv preprint here we call neuromarkers, hold promise in their potential to achieve greater classification accuracy with fewer participants than genetic biomarkers, which only explain 2.45% of risk variance even with more than 10,000 cases (9,10). However, there are several challenges to the development of robust neuromarkers.…”
Section: Introductionmentioning
confidence: 99%